Odpowiedzi

2010-02-25T20:02:41+01:00
A)
2x+5y=26|×(-3)
3x-2y=1|×2

-6x-15y=-78
6x-4y=2
+-----------------
0-19y=-76
-19y=-76|(÷-19)
y=4
b nie zrobię
2010-02-25T20:04:55+01:00
A)
2x+5y=26 /*2
3x-2y=1 /*5

4x+10y=52
15x-10y=5

4x+15x=52+5
19x=57 /:19
x=3

4*3+10y=52
10y=52-12
10y=40 /:10
y=4

x=3
y=4

b)
√2x+√3y=√3+2
x-2√2y=-√2

√2x=2
x=-√2+2√2y

√2(√2+2√2y)=2
√4+√4*√4y=2
2+2+2y=2
2y=-2 /:2
y=-1

√2x=2 /:√2
x=√1
2010-02-25T20:07:39+01:00
A)
2x+5y=26/*2
3x-2y=1/*5

4x+10y=52
15x-10y=5
+-------------
19x=57

x=3
9-1=2y

x=3
y=4

b)
√2x+√3y=√3+2
x-2√2y=-√2/*-√2

√2x+√3y=√3+2
-√2x+4y=2
+-----------------
4√3y=√3+4/:√3

4y=4

y=1
x=√2